Co-Located hepatitis C virus infection treatment within an opioid treatment program promotes opioid agonist treatment retention. (1st August 2020) - Severe, Brooke; Tetrault, Jeanette M.; Madden, Lynn; Heimer, Robert
Highlights: Opioid treatment programs (OTP) can co-locate hepatitis C virus (HCV) treatment. HCV treatment within an OTP is associated with improved opioid treatment retention. Abstract: Background: Co-located treatment for hepatitis C virus (HCV) infection for patients with opioid use disorder (OUD) within an opioid treatment program (OTP) addresses gaps in the HCV care continuum. Few reports have analyzed outcomes related to OUD treatment, such as retention, associated with co-located HCV treatment. Methods: Patients (n = 89) treated for OUD and chronic HCV infection in a Northeast US OTP from January 2014 through July 2017 were compared to control patients (n = 199) being treated for OUD and diagnosed with but not treated for HCV during the same period. All patients received opioid agonist treatment (OAT). The outcome of interest is patient retention in the OTP from January 2014 through September 2018, analyzed using logistic regression and survival analysis based on OTP loss to follow-up dates. Results: After adjusting for baseline covariates, patients who completed HCV treatment had 2.22 (95 % CI: 1.11, 4.45) increased likelihood of remaining in the OTP compared to patients in the control group. Survival analysis indicated the HCV treatment group had a significantly greater probability of being retained over the duration of the study compared with the control group. Conclusion: Results indicate that a co-located model of care is associated with improved OTP treatment retention following HCV treatment, and suggest that co-locating HCV and OUD treatment has a secondary impact on keeping patients engaged in OAT.